Measurement Issues and Behavior of Productivity Variables - Dogramaci, Ali (Springer Netherlands, 1986)
This book presents a set of papers from the leading edge of current research on productivity analysis. The focus is on alternative forms of measurement, methods, and their implications. The book begins with a chapter by V. Corbo and J. de Melo comparing the effects of using different production frontier models for measuring technical efficiency when using census data. The second chapter (by H. Pesaran and R. Tarling) is a detailed analysi·s of measurement of labor and its variations over time. The next two chapters concern the measurement of capital. The first of these is written by M. F. Mohr; the second is by B. M. Fraumeni and D. W. Jorgenson. The final chapter is by I. B. Kravis, A. W. Heston, and R. Summers and concerns the behavior of productivity and service prices. Decisions for improving productivity rely upon explicit as well as implicit assumptions on how productivity is related to a variety of factors. Determining the right relationships hinges on how these factors are measured and how the models are set. This is why better understanding of measurement issues and behavior of variables related to productivity can lead more effective policies. We plan to continue in this series to present the current research of major different schools of thought in the field
Keywords: Operations Research/Decision Theory; Operations research; Decision making; Mathematisches Modell; Produktivität; Produktivitätsmessung; USA; Aufsatzsammlung